Anti-PF4/heparin antibodies are increased in hospitalized patients with bacterial sepsis. Issue 171 (November 2018) - Maharaj, Satish; Chang, Simone
Abstract: Heparin-induced thrombocytopenia (HIT) is caused by antibodies targeting platelet factor 4 (PF4)/heparin complexes. The immune response leading to HIT remains perplexing with many paradoxes. Unlike other drug induced reactions, anti-PF4/heparin antibody generation does not follow the classic immunologic response. Research in murine models suggests that that there is close interplay among infection, PF4 and the immune system. We hypothesized there would be a relatively higher prevalence of anti-PF4/heparin antibodies in patients hospitalized for sepsis. We retrospectively examined anti-PF4/heparin antibody testing in 200 such patients. This included patients who had sepsis with bacteremia (n = 57), sepsis with fungemia (n = 7) and sepsis without bacteremia or fungemia (n = 136). For comparison, data from 50 patients without sepsis during the same time period was used. Results confirmed that patients hospitalized with sepsis have higher anti-PF4/heparin antibody levels. The groups of patients having sepsis with bacteremia, and sepsis without bacteremia, had significantly higher OD than the control group without sepsis (p < 0.05). There was no significant difference between Gram negative and Gram positive bacteremia and antibody levels. This suggests that bacterial cell wall components of both classes have similar antigenicity. Interestingly, patients who had sepsis with fungemia had much lower antibody levels compared to those with sepsis and bacteremia, and sepsis without bacteremia or fungemia. Despite the small sample size for fungemia, this difference trended strongly towards statistical significance (p = 0.05). It would be interesting to investigate this further in a larger study or using in vitro studies. In summary, there is an increased prevalence of anti-PF4/heparin antibodies in patients hospitalized with bacterial but not fungal sepsis. These results indicate that bacterial infection has a role to play in preimmunization leading to anti-PF4/heparin antibody generation. Highlights: Murine research suggests interplay among infection, PF4 and the immune system. We found bacteremia/sepsis associated with higher anti-PF4/heparin antibody titers. There was no difference between Gram negative/positive bacteremia and antibody titer. Patients who had fungemia had much lower antibody levels compared to bacteremia. Further research into anti-PF4/heparin antibodies and infection are needed.